Analisis pengaruh pertumbuhan ekonomi, pengeluaran pemerintah, upah minimum dan tingkat pendidikan terhadap tingkat pengangguran terbuka Provinsi-Provinsi di Sumatera - Angga Syahputra; Erfit Erfit; Nurhayani Nurhayani (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2019)
This study aims to: 1) To analyze the development of the open unemployment rate, economic growth, government spending, minimum wages, and the level of education of the provinces in Sumatra. 2) To find out and analyze what factors influence the income of street vendors on Jalan Basuki Rahmat to General H. Agus Salim by using panel data regression analysis tools. The development of the level of open unemployment, economic growth, and government spending in the provinces on the island of Sumatra during 2015-2017 fluctuated, however, the minimum wage and education level tended to increase. The regression results show that part, the variables of economic growth and the level of education have a significant effect on the level of open unemployment, while the variables of government spending and the minimum wage have no significant effect on the level of open unemployment in the provinces of Sumatra Island. Keywords: Open unemployment rate, Economic growth, Government expenditures, Minimum wages, Education level